Association of hip fractures with cardiometabolic‐renal risk factors in Southern Chinese patients with type 2 diabetes – the Hong Kong Diabetes Register. Issue 9 (15th March 2021) - Yun‐Ning Cheung, Elaine; Pik‐Shan Kong, Alice; Siu‐Him Lau, Eric; Yee‐Kwan Chow, Elaine; On‐Yan Luk, Andrea; Ching‐Wan Ma, Ronald; Ping Lam, Tsz; Yuk‐Wai Lee, Wayne; Chun‐Yiu Cheng, Jack; Ebeling, Peter R; Chung‐Ngor Chan, Juliana
Abstract: Introduction: Diabetes and bone health are closely related. We examined the incidence and risk factors of hip fractures in Chinese patients with type 2 diabetes (T2D). Materials and Methods: In this prospective cohort, we consecutively enrolled 22, 325 adults with T2D above the age of 40 years in the Hong Kong Diabetes Register between 1994 and 2015 with crude hip fracture incidence rate censored in 2017. Results: At baseline, the mean age of this cohort was 60.9 ± 10.5 years (mean duration of diabetes 6 years, 52.4% male). During a mean ± standard deviation (SD) follow‐up period of 8.7 ± 5.2 years with 193, 553 person‐years, 603 patients were hospitalized due to hip fractures with an incidence (95% confidence interval, CI) of 315.1 (290.4–341.3) per 100, 000 person‐years. On multivariable analysis with competing death risk adjusted, the independent hazard ratios (95% CI) for hip fractures in T2D were 2.01 (1.61–2.51) for female sex, 1.08 (1.07–1.09) for age, 0.93 (0.90–0.95) for body mass index, 1.52 (1.25–1.85) for albuminuria and 1.12 (1.02–1.23) for low density lipoprotein‐cholesterol. In men, the 30‐day, 1‐year and 5‐year post‐hip fracture mortality rate (95% CI) were 5.8 (2.4–9.1) %, 29.2 (22.3–35.5) % and 65.9 (57.3–72.8) % respectively. The corresponding rates in women were 3.4 (1.6–5.1) %, 18.6 (14.7–22.4) %, and 46.8 (40.9–52.1) %. Conclusions: Southern Chinese patients with T2D have a high risk of hip fracture associated with suboptimal cardiometabolic‐renal risk factors and a high post‐fracture mortality rate. The effects of improving modifiable risk factors on bone health warrants further evaluation. Abstract : With prospective follow up of nearly 9 years, we identified several risk factors associated with increase hip fracture incidence in Southern Chinese patients with type 2 diabetes in the Hong Kong Diabetes Register. These include female sex, age, body mass index, albuminuria and low density lipoprotein.